Immunobiology and Application of Toll-like Receptor 4 Agonists to Augment Host Resistance to Infection - Hernandez, Antonio (Pharmacol Res, 2019)
Infectious diseases remain a threat to critically ill patients, particularly with the rise of antibiotic-resistant bacteria. Septic shock carries a mortality of up to ~40% with no compelling evidence of promising therapy to reduce morbidity or mortality. Septic shock survivors are also prone to nosocomial infections. Treatment with toll-like receptor 4 (TLR4) agonists have demonstrated significant protection against common nosocomial pathogens in various clinically relevant models of infection and septic shock. TLR4 agonists are derived from a bacteria cell wall or synthesized de novo, and more recently novel small molecule TLR4 agonists have also been developed. TLR4 agonists augment innate immune functions including expansion and recruitment of innate leukocytes to the site of infection. Recent studies demonstrate TLR4-induced leukocyte metabolic reprogramming of cellular metabolism to improve antimicrobial function. Metabolic changes include sustained augmentation of macrophage glycolysis, mitochondrial function, and tricarboxylic acid cycle flux. These findings set the stage for the use of TLR4 agonists as standalone therapeutic agents or antimicrobial adjuncts in patient populations vulnerable to nosocomial infections.